Antimicrobial resistance among commensal Escherichia coli isolated from layer farmers, catfish farmers, and nonfarmers in Blitar, East Java Province, Indonesia - Titiek Sulistyowati; Tri Pudy Asmarawati; Carolien Ruesen; Heiman Wertheim; Juliëtte Severin (Journal of Global Antimicrobial Resistance)
BACKGROUND: Antimicrobial resistance (AMR) surveillance data may be collected either from clinical isolates or from isolates cultured from the commensal microflora of individuals in the absence of infection. Escherichia coli is such a commensal that is widely used as indicator. AIM: This study aimed to determine the prevalence of AMR among E. coli isolated from layer farmers, catfish farmers, and nonfarmers in the largest poultry production region in Indonesia. METHODS: Farmers and nonfarmers (i.e., public healthcare center visitors) in Blitar region, East Java, Indonesia, were approached for screening from November to December 2022. A screening consisted of a rectal swab, which was cultured on an Eosin-methylene blue (EMB) agar plate. E. coli were identified using Vitek2® (bioMérieux). Antimicrobial susceptibility testing was performed using Vitek2® and interpreted according to CLSI clinical breakpoints. RESULTS: In total, 488 individuals were screened: 121 layer farmers, 69 catfish farmers, and 298 nonfarmers. Total isolates that could be recovered were 472 E. coli. E coli from farmers and nonfarmers showed remarkably high resistance to ampicillin and trimethoprim-sulfamethoxazole (Table). The third highest was ciprofloxacin resistance: from layer farmers 9.4%, and nonfarmers 8.6%, but from catfish farmers resistance was lower (2.5%). ESBL-producing E. coli from layer farmers was 2.6%, catfish farmers 5.0%, and nonfarmers 5.1%. Carbapenem resistance was not found. CONCLUSIONS: Overall, resistance rates were considerably high for ampicillin, cotrimoxazole, and the fluoroquinolones, and mostly similar among farmers and nonfarmers. Continued monitoring of local and national resistance trends will be important, to follow trends over time.